Desingn and evaluation of a rail made of carbon fiber reinforced materal for an external fixation system (2012)
This paper introduces the design, construction, and evaluation of a rail for a unilateral external fixation system used for bone transport. The rail was made with carbon fiber/epoxy resin (CF/EP) composite material. A simple manual process was used for the construction of the element; then, the rail was evaluated via mechanical tests under axial load, bending, and torsion. The stiffness of the new element was compared with the stiffness of a commercial rail and good results were obtained.